2016
DOI: 10.1371/journal.pone.0145423
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Characterization of Au/DNA/ITO Metal-Semiconductor-Metal Diode and Its Application as a Radiation Sensor

Abstract: Deoxyribonucleic acid or DNA molecules expressed as double-stranded (DSS) negatively charged polymer plays a significant role in electronic states of metal/silicon semiconductor structures. Electrical parameters of an Au/DNA/ITO device prepared using self-assembly method was studied by using current–voltage (I-V) characteristic measurements under alpha bombardment at room temperature. The results were analyzed using conventional thermionic emission model, Cheung and Cheung’s method and Norde’s technique to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…It is a known fact that metal-semiconductive junctions constitute a Schottky junction (Schottky diode), which imparts a rectifying effect on a current-voltage (I-V) profile as observed with a conventional p-n junction 10 . The same was observed with a DNA-metal (semiconductor-metal) junction, which actually constitutes a Schottky diode, and has been published and studied in numerous research papers 11 12 13 14 15 16 . Using conventional analysis technique, various electronic parameters such as ideality factor, barrier height and series resistance can be calculated from the I-V profiles 17 .…”
supporting
confidence: 52%
“…It is a known fact that metal-semiconductive junctions constitute a Schottky junction (Schottky diode), which imparts a rectifying effect on a current-voltage (I-V) profile as observed with a conventional p-n junction 10 . The same was observed with a DNA-metal (semiconductor-metal) junction, which actually constitutes a Schottky diode, and has been published and studied in numerous research papers 11 12 13 14 15 16 . Using conventional analysis technique, various electronic parameters such as ideality factor, barrier height and series resistance can be calculated from the I-V profiles 17 .…”
supporting
confidence: 52%
“…It is understood that tracks are formed upon bombardment of alpha particles. These tracks involve an increase in the number of charges due to the linear energy transfer (LET) from the alpha particle 34 45 46 . As a result of a large number of material excitation by these particles along its path, an increase in the number of charges can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported on Schottky barriers of DNA/metal structures prepared by simple casting of aqueous DNA solutions. While some reported properties of a metal–semiconductor junction, metal–insulator junctions have also been reported . Here, the HBP-SAs were embedded in commercially available Pt-IDA devices, and the Pt/DNA/Pt structures were characterized with two-terminal mode I – V measurements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…According to Chan et al, Au/DNA/ITO devices exhibited a similar ϕ b = 0.796 eV and n = 15.0 when the DNA extracts from Mimosa pudica were used . Al-Ta’ii et al prepared Au/DNA/ITO devices using mushroom DNA extracts and reported a ϕ b = 0.6679 eV and n = 8.8803 . Furthermore, Periasamy et al examined seven edible mushroom DNAs and found that their electronic parameters were significantly different from each other; they claimed that the finding was useful for identifying DNAs .…”
Section: Results and Discussionmentioning
confidence: 99%